The Role of Individual Characteristics, Work Life Balance and Work Discipline on Employee Performance - Roehati, Cicih; Syahfira, Maflikhatus; Sulistiyowati, Lisa Harry (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The objective of this research is to explore and assess the extent to which individual traits, the harmony between occupational and personal responsibilities, as well as adherence to organizational policies, influence the productivity of employees in Regional Public Companies located in West Java. This investigation utilized a quantitative approach, engaging a total workforce of 140 individuals. Following the exclusion of directors and non-permanent staff, the final sample comprised 130 respondents who filled out a structured questionnaire. The analysis of the data demonstrated that each of the three examined aspects significantly affects employee output. The statistical outcomes indicated that individual characteristics, work-life integration, and compliance with company regulations notably contribute to employee productivity, as evidenced by a significance value of 0.001, which is well below the 0.05 threshold, and t-values greater than 1.978. Moreover, the determination coefficient (R²) stood at 0.983, signifying that 98.3% of the variation in performance could be attributed to the studied variables, while only 1.7% was linked to other influences. Additionally, the correlation coefficient (R) was recorded at 0.992, reflecting a very high positive association 99.2% between the measured aspects and work performance. These results underscore the necessity of fostering a supportive work setting, encouraging favorable personal attributes, and maintaining organizational discipline to enhance employee effectiveness within Regional Public Companies in the West Java region.